Experience with artificial intelligence algorithms for the diagnosis of vertebral compression fractures based on computed tomography: from testing to practical evaluation - Zlata R. Artyukova; Alexey V. Petraikin; Nikita D. Kudryavtsev; Fedor A. Petryaykin; Dmitry S. Semenov; Daria E. Sharova; Zhanna E. Belaya; Anton V. Vladzimirskyy; Yuriy A. Vasilev (Digital Diagnostics)
BACKGROUND: Osteoporosis is often diagnosed at the stage with complications, i.e., low-energy fractures. Vertebral compression fractures, which are complications of osteoporosis and predictors of subsequent fractures, are often asymptomatic. Compression fractures can be found by computed tomography performed for other indications with vertebral morphometry. Approaches to using artificial intelligence algorithms designed for diagnosing vertebral compression fractures were analyzed.